ANALISIS KINERJA KEUANGAN DAN KINERJA INVESTASI TERHADAP KINERJA PORTOFOLIO SAHAM SERTA TAX PLANNING SEBAGAI VARIABEL MODERATING - Eduwinsah, Nurman; Sitorus, Riris Rotua (Universitas 17 Agustus 1945 Jakarta, 2018)
This study aims to analyze the effect of financial performance and investment performance on stock portfolio performance and tax planning as a moderating variable and to know the variables that have dominant influence by collecting publication data of annual financial reports of manufacturing companies that have been listed on BEI and in accordance with sample selection criteria. Independent variables are financial performance and investment performance. the dependent variable is stock portfolio performance and tax planning as moderating variable. The location of the research is a company listed on the BEI. The population in this study is manufacturing companies listed on the BEI selected as the research population due to this sector average sales per year always increased. The sample selection used for this research is purposive sampling method. This method selects the sample to focus on a specific purpose. Data obtained from BEI which then processed and analyzed by using data analysis STATA.The results of this study indicate that the variables of financial performance, investment performance, and tax plannig have a significant effect on stock portfolio performance. Variable tax planning is not able to moderate the financial performance and investment performance on stock portfolio performance.Keywords; financial performance, investment performance, tax planning, stock portfolio performance.